Modifikasi Metode Preparasi Pewarnaan Akar untuk Deteksi dan Visualisasi Pembentukan Koloni Fungi Mikoriza Arbuskula (FMA) - Susan Irmayanti; Inggit Winarni (LPPM Universitas Terbuka, 2022)
The root staining method was used to detect the presence of Arbuscular Mycorrhizal Fungi (AMF) and to calculate the colonization of the AMF in the roots. Optimal root staining methods not only help in the study of plant-associated mycorrhizae, but also save time and money. Root staining aims to clarify and sharpen the picture of AMF associated with plants on the roots, making it easier to observe with a light microscope. This study aims to obtain an effective (fast, safe, and economical) and flexible method of preparation of root staining so that the visualization of AMF on roots becomes clear and contrasting. The method used in this research is descriptive qualitative which includes the cleanliness of the roots from cell contents, root texture, and color contrast, which consists of three treatments, namely P1 (control) using 10% KOH with 90°C heating and followed by the modified Philips & Hayman staining procedure (1970), P2 using 5% KOH by heating at 90°C followed by the modified Philips & Hayman (1970) procedure using 1% HCl, and P3 using 5% KOH heating at 90°C then stained followed the staining method of Philips & Hayman (1970) which was modified by the use of commercial vinegar as a substitute for HCl. All treatments used Trypan Blue dye. The results showed that the P2 and P3 treatments showed results that were not different from P1, the state of the roots is clean enough thereby detection and visualization of AMF could still be observed properly. The P3 treatment method with heating for 9 minutes can be an alternative method that is effective (fast, safe, economical) and flexible. It faster than common method because it takes 9 minutes for cleaning root cells, relatively safe with the use of commercial vinegar solution to replace HCl solution, and economical because it can reduce the need for KOH material up to 50%.